República Argentina, Océano Atlántico Sur, Islas Orcadas del Sur / compilación de levantamientos nacionales y extranjeros - Argentina. Dirección General de Navegación e Hidrografía (Argentina. Ministerio de Marina, 1964)
1a edición 1952. Última corrección . 1964 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines, bathymetric tints and soundings.; Includes tidal and conversion tables.; Selected lights shown in purple.; "I.B. de Etchepare Cartógrafo" -- lower right margin.; "117." Color 1:200,000